CONTEXTUAL CLASSROOM EXPERIENCE THROUGH GENRE BASED APPROACH - Assidqi, MA Hakim (Vision: Journal for Language and Foreign Language Learning, 2015)
This paper is formulated to elaborate the understanding ofGenre Based Approach as the part of Systemic Functional Lin-guistic infl uence. SFL has been developed by Halliday that focuson function and meaning as the core aspects. Because of its infl u-ence in linguistic, SFL gives inspiration for inventing GBA, as thekind of approach in language learning. The aims of the study areto explore the base understanding of GBA from its historical anddevelopment perspective. In addition, the paper is trying to analyzethe main points of GBA and its impact to improve learner skills inclassroom activity for some skills, they are writing, reading, speakingand listening.